Education for Sustainable Development: Understanding by Physical Education and Sports Specialists - Halyna Tsyhura; Serhii Harkusha (OVS LLC, 2023)
Study purpose. The purpose of the study was to investigate the need for physical education and sports specialists to acquire competencies for the organization of educational activities for sustainable development and their understanding of the involvement of the field of physical education and sports in the implementation of sustainable development goals. Materials and methods. The study involved 106 specialists in physical education and sports from various regions of Ukraine (73 women and 33 men). The participants comprised representatives of general secondary education institutions (schools, lycées, gymnasiums) - 70.7% of the respondents (75 persons), representatives of higher education institutions (universities and academies) - 11.3% of the respondents (12 persons), representatives of sports institutions (youth sports schools and sports complexes) - 10.4% of the respondents (11 persons), representatives of vocational education institutions (schools, colleges) and out-of-school youth work centers - 7.5% of the respondents (8 persons). The respondents' work experience in the field of physical education and sports ranged from 1 to 45 years. The study used the methods of surveying, analysis and synthesis of information, and mathematical information processing. Results. The survey revealed that most of the respondents are not sufficiently familiar with the issues of sustainable development. 51.89 % of the respondents indicate partial awareness of the concept and sustainable development goals, 5.66 % claim that they are not familiar with such information at all. The majority of the physical culture and sports specialists who participated in the experiment do not understand the essence and depth of Sustainable Development Goals and only link physical education and sports to such Sustainable Development Goals as good health and well-being (Goal 3), quality education (Goal 4), and gender equality (Goal 5). Conclusions. It was found that only 3.8% of the respondents can find a correlation between the field of physical education and sports and the seventeen Sustainable Development Goals. 62.26% of the respondents indicate that they need to expand their knowledge and skills on sustainable development, 46.23% of the respondents want to deepen the knowledge and skills in the methodology of implementing education for sustainable development. Most of the surveyed physical education and sports specialists need advanced training to acquire the competencies necessary for the implementation of educational activities for sustainable development.